2020
DOI: 10.1038/s41598-020-71676-6
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and the risk of rheumatoid arthritis: a systematic review and meta-analysis of cohort studies

Abstract: Several studies have investigated associations between overweight/obesity and risk of developing rheumatoid arthritis, however, the evidence is not entirely consistent, and previous meta-analyses mainly included case–control studies, which can be affected by various biases. We therefore conducted a systematic review and meta-analysis of cohort studies on adiposity and risk of rheumatoid arthritis. Relevant studies were identified by searching PubMed and Embase databases. Random effects models were used to esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Indeed, we have shown elevated prevalence of autoimmune disorders (namely T1DM, inflammatory bowel diseases, rheumatoid arthritis, and hypothyroidism) in two independent BBS cohorts. Obesity potentially contributes to the increased prevalence of autoimmune diseases in BBS patients, as obesity is associated with high prevalence of hypothyroidism, Hashimoto's thyroiditis, and rheumatoid arthritis (Song et al , 2019; Ohno et al , 2020). We also observed alteration of the white blood cell count in BBS patients and in a BBS mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have shown elevated prevalence of autoimmune disorders (namely T1DM, inflammatory bowel diseases, rheumatoid arthritis, and hypothyroidism) in two independent BBS cohorts. Obesity potentially contributes to the increased prevalence of autoimmune diseases in BBS patients, as obesity is associated with high prevalence of hypothyroidism, Hashimoto's thyroiditis, and rheumatoid arthritis (Song et al , 2019; Ohno et al , 2020). We also observed alteration of the white blood cell count in BBS patients and in a BBS mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also demonstrated that even being overweight (BMI>25) increased risk of RA, especially in adults less than 50 years of age [ 26 ]. Others have suggested the association between increased BMI and RA is greatest for women [ 27 29 ] or smokers [ 29 ].…”
Section: Obesitymentioning
confidence: 99%
“…Factors related to obesity may also increase risk of RA. A more recent meta-analysis showed not only BMI but also increased weight circumference increased risk of RA [ 27 ]. Along similar lines, a large cohort study within the Nurse’s Health Study showed that physical activity dramatically reduced the risk of later developing RA, with BMI mediating only 14% of this effect [ 30 •].…”
Section: Obesitymentioning
confidence: 99%
“…Supported by previous studies, we know a high BMI is linked to increased disease activity and disability at disease onset, being an independent factor of less responsive to therapy [ 42 , 43 ]. However, not all studies led to a common conclusion, and some of them gave inconsistent results [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that these different adipose tissue depots showed metabolic implications and effects [ 45 ]. The former has been more commonly linked to hypertension and T2D, while the latter conferred a neutral or even protective effect against metabolic disease [ 44 ].…”
Section: Resultsmentioning
confidence: 99%